REHABILITATION EQUIPMENT FOR MOTOR FUNCTION RECOVERY AND RESTORATION AFTER INJURIES - Мустафина, Канисса; Танабай, Жанна (SWorldJournal, 2024)
The article presents a review of modern simulators for restoring motor activity after injuries. As the number of injuries caused by accidents and sports damages increases, there is a growing interest in developing innovative rehabilitation methods. Simula